Multimodal Gestalts and Post-pandemic Utopianism: Drum and Bass on the Bike - Rivers, Damian J. (Frontiers in Communication, 2022)
Framed within a society insidiously damaged by the novel coronavirus pandemic and associated lockdown restrictions, this article examines the drum and bass on the bike initiative of British DJ Dom Whiting. The initiative comprises of Dom riding a tricycle through various urban landscapes while broadcasting live to social media from onboard mixing decks. Since the first two rides in 2021 where Dom rode solo, thousands of individuals have accompanied him through twelve urban landscapes in addition to millions more participating across social media through views, comments, likes, and shares. Situating YouTube uploads as text, and positioning Dom as a harmonic navigator of change and reformation in the urban space, the article draws from a social semiotic multimodal approach to communication and details the development of three multimodal gestalts indicative of post-pandemic society. Against a soundtrack of thunderous drum and bass music, the three emergent gestalts communicate post-pandemic utopianism through the reformation of the relationship between motor vehicle drivers and cyclists, the reformation of urban road space use, and the reformation of diversity in organized cycling events.